1998
DOI: 10.1159/000009913
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Big Endothelin-1 and Characterization of Its Contractile Effects on Isolated Human Placental Arteries

Abstract: Objectives: To study the conversion of human big endothelin-1 (bigET-1) to endothelin-1 (ET-1) and to characterize contractile ET-1 receptors in human placental arteries. Methods: BigET-1 was incubated with artery membranes and the formation of ET-1 was investigated. ET-1 and bigET-1-induced contractile responses were studied in the absence or presence of the metalloprotease inhibitor phosphoramidon, the ETA-receptor antagonist BQ 123, or the ETB-receptor antagonists IRL 1038 and RES 701-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Interestingly, the onset of contraction and the increase in tone are slow upon application of big ET-1 when compared to ET-1. This observation suggests the involvement of an enzymemediated step in the contractile action of exogenously applied big ET-1 as previously observed in other vascular tissues such as the rabbit aorta [16] , the human umbilical vein [17] , the human placental artery [18] and the rat basilar artery [15] . Additionally, our results show that phosphoramidon, a non-selective inhibitor of ECE and neutral endopeptidase, produces rightward displacements of the big ET-1 concentration-response curves with a reduction in the maximal response, further indicating that this peptide must be converted to exert its biological activity.…”
Section: Synthesis and Expression Of Et In The Rat Carotidsupporting
confidence: 83%
“…Interestingly, the onset of contraction and the increase in tone are slow upon application of big ET-1 when compared to ET-1. This observation suggests the involvement of an enzymemediated step in the contractile action of exogenously applied big ET-1 as previously observed in other vascular tissues such as the rabbit aorta [16] , the human umbilical vein [17] , the human placental artery [18] and the rat basilar artery [15] . Additionally, our results show that phosphoramidon, a non-selective inhibitor of ECE and neutral endopeptidase, produces rightward displacements of the big ET-1 concentration-response curves with a reduction in the maximal response, further indicating that this peptide must be converted to exert its biological activity.…”
Section: Synthesis and Expression Of Et In The Rat Carotidsupporting
confidence: 83%
“…It is well established that BigET‐1 must be converted to ET‐1 to exert its biological activity. Accordingly, phosphoramidon, a nonselective ECE/NEP inhibitor, reduces the contraction induced by BigET‐1 in several vascular tissues (Maguire et al ., 1997; Hanson et al ., 1998) as well as the levels of mature ET‐1 in the bathing medium after addition of the 38 amino acids precursor (Maguire et al ., 1997). Our results show that phosphoramidon produced rightward displacements of the BigET‐1 concentration–response curves with reduction of the maximal response, further indicating that this peptide must be converted to exert its biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the above‐mentioned observations, which organs/tissues are predominantly implicated in the generation of ET‐1(1–31) from exogenous BigET‐1 in the rabbit (or in any other species for that matter) still remains to be elucidated. Functional experiments in a variety of vascular tissues, such as the human umbilical vein (Maguire et al ., 1997), the human placental artery (Hanson et al ., 1998) and the rat basilar artery (Zimmermann et al ., 2002), previously showed that the contraction induced by BigET‐1 was sensitive to phosphoramidon, thus supporting a role for the vascular system in the generation of ET peptides. Interestingly, a similar role for chymase has been proposed in the processing of angiotensin I to angiotensin II in the rabbit aorta (Akasu et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%